Unified treatment of Artin-type problems - Järviniemi Olli; Perucca Antonella (Springer, 2025)
Since Hooley's seminal 1967 resolution of Artin's primitive root conjecture under the Generalized Riemann Hypothesis, numerous variations of the conjecture have been considered. We present a framework generalizing and unifying many previously considered variants, and prove results in this full generality (under GRH).